La Eficacia y el Control en la que se Configura el Delito de Estafa en Compraventa de Bienes Raíces - Armijos Armijos, Jhonatan José (2022)
The general objective in the present topic is to determine the swindle as a crime against property, or damage to patrimony. In the present topic we orient this crime to the investment of real estate companies in charge of residential plans, or housing plans with the purpose of delivering benefits to its partners through payment facilities, these can be lots, lands, condominiums etc., In Article 186 of the Código Orgánico Integral Penal we can determine it as swindle, since sometimes it is not fulfilled, and it is produced through deceit, swindle, fraud, lie, and error, according to what is established in general terms by the different types of legislations. The crime of swindle is described as an act of damage or harm on the property or patrimony of another person, regardless of the variety of types of swindle makes it possible, all these types cause damage, in such a way, by causing harm to others, in this part should be considered extremely high penalties for people who perform these acts. In our Ecuadorian legislation through the Código Orgánico Integral Penal, Art 186, fraud is considered as a crime by which a person who, in order to obtain a patrimonial benefit for him/herself or for a third person, through the simulation of false facts or the deformation or concealment of true facts, induces another person to error, with the purpose of making him perform an act that harms his patrimony or that of a third person, will be punished with imprisonment from five to seven years. In this part there is a resemblance between fraud and swindling, which includes a series of crimes, but most of them are included within two species, that is, basically fraud, swindling, and deception produced through elements that contain this crime, the error is an indisputable part of this act, which is carried out through the aforementioned. The difference appears notably, at the moment that the active subject by means of his act when acting painfully, in the swindle, with malice basically getting to know the damage that can generate, causes it later when proceeding to carry out the swindle, the consequences in certain point can be irreparable, or in other occasions the damage caused can be compensated, that is to say, the passive subject delivers a good, real thing by his own will through false facts or elements that persuaded the victim, the passive subject, by means of the lie as a result of it the seriousness of the fact is produced generating material loss to his patrimony, economically, affecting directly to the property, having delivered something of his property.